G514(P) Benefits of patient feedback in quality improvement of a local cystic fibrosis service. (May 2019) - Berry, L; Newson, TP; Smith, O
Abstract : Aim: Evaluate the impact of patient and family feedback in quality improvement of a Local Cystic Fibrosis Service. Background: Cystic Fibrosis [CF] is a complex chronic disease which mandates patients and families to take on a heavy burden of treatment and regular attendance at clinics with many children requiring intensification of treatment in hospital or hospital at home [home IVs].Emphasis tends to be on a medical model of care which can mean parental or patient experience is not sufficiently considered in developing the service. In 2016 we started getting regular parental and parent feedback to help improve our service. Methods: An anonymous questionnairre based on the CF Trust Standards of care was devised and then given to parents or patients in clinic or by post. In 2016 n=23 responses [78%] and 2017 n=22 responses [100%] out of 38 patients looked after by service. Results: Table 1 CF Trust standards feedback. Suggestions from surveys were many but main themes were: improve communication between ward and community, better contact between community and hospital physiotherapist, local annual blood test would be good, community nurses communication, and use reminder texts and letters for appointments. Outcome: Following each questionairre a series of recommendations and action plans were drawn up to improve care. Make accessible Team in Clinic if not available follow up with telephone contact Reduce repetitive questioning in clinic Improve staff hand hygiene Feedback issues of cleanliness to ward Review food availiable on ward re: CF requirements Improve inpatient physiotherapy Improve communication between ward and community Joint working with Tertiary Centre eg local bloods Enhance Community support and have Parent representative on CF MDM Meeting. Conclusion: Parental and patient feedback is useful in both assessing a CF service but also looking for ways to develop and improve the patient experience. Feedback to patient and families about the changes we have made and improvements to address the issues raised by the survey is equally important in making the process of engaging with families a meaningful ongoing partnership.